2019
DOI: 10.1007/s11892-019-1205-7
|View full text |Cite
|
Sign up to set email alerts
|

Care of Children and Adolescents with Diabetes Mellitus and Hyperglycemia in the Inpatient Setting

Abstract: Purpose of Review Children and adolescents with acute hyperglycemia and diabetes mellitus frequently have acute, potentially life-threatening presentations which require high-acuity care in an inpatient and often intensive care setting. This review discusses the evaluation and care of hyperglycemia and diabetes mellitus in hospitalized children in both critical and non-critical care settings, highlighting important differences in their care relative to adults. Recent Findings Diabetic ketoacidosis remains high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Although HHS patients often present with AMS due to high serum osmolality, prior studies have shown that their risk of cerebral edema is actually lower than in DKA, where cerebral edema is the main cause of morbidity and mortality. 2,10,15 Nonetheless, HHS patients remain at theoretical risk of cerebral edema if serum osmolality and corrected sodium decline too rapidly. Osmolality decreases of 3 mOsm/h and sodium decreases of 0.5 mEq/L per hour should be targeted.…”
Section: Hhs Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although HHS patients often present with AMS due to high serum osmolality, prior studies have shown that their risk of cerebral edema is actually lower than in DKA, where cerebral edema is the main cause of morbidity and mortality. 2,10,15 Nonetheless, HHS patients remain at theoretical risk of cerebral edema if serum osmolality and corrected sodium decline too rapidly. Osmolality decreases of 3 mOsm/h and sodium decreases of 0.5 mEq/L per hour should be targeted.…”
Section: Hhs Complicationsmentioning
confidence: 99%
“…13 In children with HHS or mixed HHS/DKA with concern for cerebral edema, mannitol and hypertonic saline can be considered, with the caveat that hypertonic saline administration will likely worsen osmolality corrections. 13,15 "Hyperglycemic hyperosmolar syndrome places children at far greater risk for thrombosis than DKA. This is primarily due to hyperosmolar damage to endothelial cells and dehydration directly upregulating coagulation factors.…”
Section: Hhs Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…DKA is frequently encountered in daily clinical practice, in both newly diagnosed cases (up to 70%) and patients with established type 1 diabetes (T1D) (rate, 1-10% per case per year) [2]. The common risk factors for DKA include new diagnosis of T1D, young children, adolescent female patients, delayed T1D diagnosis, insulin omission, poor treatment on a sick day, accessibility to hospitals, and insulin pump injection errors [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%